2016
DOI: 10.1080/17445647.2015.1135301
|View full text |Cite
|
Sign up to set email alerts
|

Snæfellsjökull volcano-centred ice cap landsystem, West Iceland

Abstract: A 1:10,526 scale map of Snaefellsjökull and its forelands is presented as the first landsystem exemplar of volcano-centred ice caps, for application to understanding glacierized volcanic terrains globally. Mapping of surface materials and landforms was undertaken using orthorectified aerial photographs taken in 2002 and results of ground truth fieldwork in 2010. Nine natural surficial geology units were identified in addition to bedrock, glacier ice and made ground associated with pumice mining. The spatial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(46 reference statements)
1
9
0
Order By: Relevance
“…The boulder walls within M8, M9 and MA are also consistent with minor frontal re-advances into a boulder field and the bulldozing of small ridges. Flutings are visible between the MB ridges, similar to the landform pattern observed at active temperate glacier margins in Iceland (Evans and Twigg, 2002;Evans, 2003b;Chandler et al, 2016aChandler et al, , 2016bEvans et al, 2016aEvans et al, , 2016bEvans et al, , 2017. The presence of annual moraines suggests that, up to 2005 at least, Charquini Sur had a seasonally-oscillating active margin.…”
Section: The Glacial Landsystem Of a Tropical Glaciersupporting
confidence: 59%
See 4 more Smart Citations
“…The boulder walls within M8, M9 and MA are also consistent with minor frontal re-advances into a boulder field and the bulldozing of small ridges. Flutings are visible between the MB ridges, similar to the landform pattern observed at active temperate glacier margins in Iceland (Evans and Twigg, 2002;Evans, 2003b;Chandler et al, 2016aChandler et al, , 2016bEvans et al, 2016aEvans et al, , 2016bEvans et al, , 2017. The presence of annual moraines suggests that, up to 2005 at least, Charquini Sur had a seasonally-oscillating active margin.…”
Section: The Glacial Landsystem Of a Tropical Glaciersupporting
confidence: 59%
“…The Charquini Sur cirque glacier landsystem shares more characteristics with the high-mountain (alpine) clean glacier end-member of the glaciated valley landsystem, as synthesized by Benn et al (2003). Evans et al, 2006aEvans et al, , 2006bEvans et al, , 2016aEvans et al, , 2016bEvans, 2010), have also been reported from other high-mountain, clean glaciers (e.g. Annual moraines and/or fluted intermorainic zones, typical at lowland clean valley glaciers (e.g.…”
Section: Zonation Within the Landsystemmentioning
confidence: 59%
See 3 more Smart Citations